A canção de protesto e o rock protesto: diálogos da democracia brasileira - Sorroce, Danilo Sérgio (2015)
During this study we focused our research on dialogues between the Protest Song of 1960s and 1970s, especially those occurred in certain works created by Gilberto Gil, Caetano Veloso and Chico Buarque de Holanda and a few songs produced by politicized and protest rock launched by bands from Brasilia such as Capital Inicial, Plebe Rude and Legião Urbana in the 1980s, contextualizing this cultural production within an important period in the recent history of Brazil. Through the theory developed by Bakhtin, we were confronted with dialogues between speakers and speeches, which allowed us to produce analysis of the characteristics and content of the dialogues between the "Old" Protest and the "New" Protest. The investigation allowed us to point out some similarities between the songs analyzed, and also enabled us to interpret them as articulating elements of the period in which they arose, which is evident in the performance of songs from both periods as a political tool of contestation.